Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1590/1983-21252020v33n404rc
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Rates and Multifunctional Microorganisms in a Tropical Flooded Rice Crop

Abstract: Tropical flooded rice production systems require a high input of fertilizers and chemical defensive. The use of plant growth-promoting rhizobacteria (PGPR), a sustainable component of this system, can increase nutrient-use efficiency and lead to significant increases in the grain yield of tropical flooded rice crop. This study aimed to determine the effect of the microorganism BRM 32110 (Bacillus thuringiensis) in combination with nitrogen (N), phosphorus (P) and potassium (K) application rates on the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The application of multifunctional microorganisms improves plant development through direct and indirect mechanisms, and has shown that it is possible to make crop management practices more environmentally sustainable (Cruz et al, 2023;Silva et al, 2023). These mechanisms are a result of production of specific metabolites, such as growth stimulants (phytohormones), hydrolytic enzymes, siderophores, antibiotics, and carbon and nitrogen hence acting as a growth promoter (Silva et al, 2022;Rezende et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The application of multifunctional microorganisms improves plant development through direct and indirect mechanisms, and has shown that it is possible to make crop management practices more environmentally sustainable (Cruz et al, 2023;Silva et al, 2023). These mechanisms are a result of production of specific metabolites, such as growth stimulants (phytohormones), hydrolytic enzymes, siderophores, antibiotics, and carbon and nitrogen hence acting as a growth promoter (Silva et al, 2022;Rezende et al, 2021).…”
Section: Introductionmentioning
confidence: 99%